Critical Analysis on the Role of Nidra in the Maintenance of Health - An Ayurvedic Review (International Journal of Ayurveda and Pharma Research, 2024)
Sleep which is often considered to be a “passive activity” is increasingly being recognized as an essential aspect in both heath promotion as well as prevention of chronic diseases. Insufficient sleep, either directly or indirectly, is associated with a number of chronic diseases such as diabetes mellitus, cardiovascular diseases, obesity as well as depression. Insufficient sleep is associated with the onset of these diseases and also posses’ important implications for their management and its outcome. Ayurveda considers Nidra as one among the Trayo upasthambha’s along with Ahara and Brahmacharya. These 3 factors maintained in optimum quantity and quality is essential for living a healthier disease free life. Lack of sleep is considered as Nidranasha in Ayurveda which is attributed to the development of multiple chronic life style disorders in longer run. The role of improper Nidra in the development of different chronic diseases should be understood properly to prevent the damage from them and to promote healthy living among the human beings around the world.